Instrumented classification of patients with early onset ataxia or developmental coordination disorder and healthy control children combining information from three upper limb SARA tests. (September 2021) - Dominguez-Vega, Zeus T.; Dubber, D.; Elting, Jan Willem J.; Sival, D.A.; Maurits, Natasha M.
Abstract: Background: Early Onset Ataxia (EOA) and Developmental Coordination Disorder (DCD) share several phenotypical characteristics, which can be clinically hard to distinguish. Aim: To combine quantified movement information from three tests obtained from inertial measurements units (IMUs), to improve the classification of EOA and DCD patients and healthy controls compared to using a single test. Methods: Using IMUs attached to the upper limbs, we collected data from EOA, DCD and healthy control children while they performed the three upper limb tests (finger to nose, finger chasing and fast alternating movements) from the Scale for the Assessment and Rating of Ataxia (SARA) test. The most relevant features for classification were extracted. A random forest classifier with 300 trees was used for classification. The area under the receiver operating curve (ROC-AUC) and precision-recall plots were used for classification performance assessment. Results: The most relevant discerning features concerned smoothness and velocity of movements. Classification accuracy on group level was 85.6% for EOA, 63.5% for DCD and 91.2% for healthy control children. In comparison, using only the finger to nose test for classification 73.7% of EOA and 53.4% of DCD patients and 87.2% of healthy controls were accurately classified. For the ROC/precision recall plots the AUC was 0.96/0.89 for EOA, 0.92/0.81 for DCD and 0.97/0.94 for healthy control children. Discussion: Using quantified movement information from all three SARA-kinetic upper limb tests improved the classification of all diagnostic groups, and in particular of the DCD group compared to using only the finger to nose test. Highlights: SARA upper limb subscores are assessed in patients with EOA, DCD and controls. Kinetic ataxic features are determined with inertial sensors and quantified. Combining three SARA tasks improves classification compared to one task. Results may help distinguish between EOA and DCD in clinical practice.